Patients’ Views on a Combined Action Observation and Motor Imagery Intervention for Parkinson’s Disease - Judith Bek; Jordan Webb; Emma Gowen; Stefan Vogt; Trevor J. Crawford; Matthew S. Sullivan; Ellen Poliakoff (Parkinson's Disease)
Background. Action observation and motor imagery activate neural structures involved in action execution, thereby facilitating movement and learning. Although some benefits of action observation and motor imagery have been reported in Parkinson’s disease (PD), methods have been based on stroke rehabilitation and may be less suitable for PD. Moreover, previous studies have focused on either observation or imagery, yet combining these enhances effects in healthy participants. The present study explores the feasibility of a PD-specific home-based intervention combining observation, imagery, and imitation of meaningful everyday actions. Methods. A focus group was conducted with six people with mild to moderate PD and two companions, exploring topics relating to the utility and feasibility of a home-based observation and imagery intervention. Results. Five themes were identified. Participants reported their experiences of exercise and use of action observation and motor imagery in everyday activities, and the need for strategies to improve movement was expressed. Motivational factors including feedback, challenge, and social support were identified as key issues. The importance of offering a broad range of actions and flexible training was also highlighted. Conclusions. A home-based intervention utilising action observation and motor imagery would be useful and feasible in mild to moderate PD.